An international online survey on extent of phubbing and its correlates (Journal of Psychiatrists' Association of Nepal, 2024)
Introduction: Phubbing can be described as an individual looking at his or her mobile phone during a conversation with other individuals, dealing with the mobile phone and escaping from interpersonal communication. Being a new concept, research on its correlates is limited. The aims of the study were to find the extent of phubbing and its correlates.Material & Methods: It was an online survey through Google forms with cross-sectional design and convenience sampling. Those above 18 years who were willing to participate and provided consent were included. The questionnaire included socio-demographic and clinical details, Patient health questionnaire (PHQ-4), and couples ‘satisfaction index (CSI) scale. Descriptive statistics, group comparisons, and Pearson's correlation were done.Results: 904 participants (463 from India, 224 from Nepal, 132 from Indonesia, others 85) were included in the study. 2.3% had a higher likelihood of phubbing. The total phubbing score showed a statistically positive significant correlation with the duration of internet use (p